Social Inequality and Solidarity in Times of COVID-19 - Stok, F. Marijn (Int J Environ Res Public Health, 2021)
The enormous public health burdens of the COVID-19 pandemic are not distributed equally. Inequalities are noticeable along socio-economic and socio-cultural fault lines. These social determinants of health affect both the prevalence and severity of COVID-19 infections as well as the magnitude of negative impacts of the measures taken to slow the spread of the virus. This perspective paper summarizes key inequalities in who is affected by SARS-CoV-2 infection and in who is affected by COVID-19 prevention measures, based on evidence presented in state-of-the-art literature, and discusses the scope of challenges that these inequalities pose to solidarity and social justice. Key challenges for solidarity are highlighted across three areas: challenges to intergenerational solidarity, to global solidarity, and to intergroup solidarity.